Impact of Federalism on District Market: A Case Study of Charikot - KC, Shanta Bahadur; Shrestha, Karuna (Tribhuvan University Journal, 2025)
This study aims to examine the factors that contribute to establishment of business sustainability to the long-term survival of businesses in the markets of Dolakha district, specifically in Charikot bazaar after the adoption of federalism. The study uses descriptive research design including questionnaires and field observations tools. The major source of data is sample survey. The main findings of the study show the existing ongoing business in Charikot market, status of involvement of businessmen, the type of business, the returns earned from the existing businesses founded at different times using various funding sources, and the state of interest rates. Furthermore, with the introduction of federalism, the market is influenced by several causes such as market decentralization, increasing interest rates, diminishing business, low return, high rental rates and so on, which had an impact on the continued operation of businesses in the market. Eventually, the study indicates that federalism has both positive and negative effects on district markets, influencing aspects such as market competitiveness, local governance arrangements and economic possibilities. However, the study also found that implementing federalism confronts challenges. To overcome those challenges, the local government must enforce the reviving measures of migrated and discontinued business through formulate effective policies and policymaker must improve the trade policy. Promoting tourism destinations, establishing high-quality educational institutions, providing lower interest rates, and extending payment periods to support ongoing commercial operations are the major reviving measures of business sustainability in Charikot market.